Temporal distortion for angry faces: Testing visual attention and action preparation accounts. - Tipples, Jason; Lupton, Michael; George, David (Quarterly Journal of Experimental Psychology, 2024)
When asked to judge the duration of a face people typically overestimate the duration of angry compared with neutral faces. A novel feature of the current research was the inclusion of secondary manipulations designed to distort timing performance namely the effects of visual cues (Experiment 1) and action preparedness (Experiment 2). Furthermore, to establish whether the effects are multiplicative with duration, the effects were examined across two duration ranges (200–800 and 400–1,600 ms). Visual cues and instructions to prepare to act increased the tendency to judge faces as lasting longer. Experiment 1 revealed an unexpected underestimation effect for angry faces presented for short durations (200–800 ms). However, the effect was not replicated in Experiment 2 where the results were generally consistent with either an increase the speed of a pacemaker mechanism that resides within an internal clock or the widening of an attentional gate—the temporal overestimation effect for angry faces grew in magnitude from the short to long duration. Experiment 2 also showed that the temporal overestimation for angry faces was reduced in magnitude when participants were asked to prepare to either push or pull a joystick.